Socio-demographic determinants of male involvement in maternal and child healthcare in Rivers East Senatorial District of Rivers State - Peter-Kio, Opirite Boma; Obisike, Mary Henjieru (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
Maternal and child health (MCH) issues are among the critical global health burdens threatening underdeveloped nations, especially African countries where patriarchal tendencies are deeply rooted. This study, therefore, investigated the socio-demographic determinants of male partner involvement in maternal and child health care in the Rivers East Senatorial District of Rivers State. The descriptive correlational research design was adopted with a population consisting of 109,235 married men in the Rivers East Senatorial District. A sample size of 1,197 was selected using the multi-stage sampling procedure. Data were collected using a questionnaire with a reliability coefficient of 0.84 and analyzed using mean and linear regression models at 0.05 alpha level. The result showed a high extent (3.45±0.64) of male involvement in components of maternal and child healthcare. A high positive relationship was found between male involvement and socio-demographic variables such as age (r = 0.97), occupation (r = 0.93) and educational level (r = 0.96). The tested hypotheses revealed that a statistically significant relationship was found between male involvement and all the factors listed above (p<0.05). It was concluded that male involvement in maternal and child healthcare is determined by the socio-demographic characteristics (age, occupation and educational level of the men). It was recommended among others that, public Health Educators should organize sensitization programmes aimed at reaching out to older as well as young male partners through church and market outlets to encourage their participation.